Knowledge of Physics Subject Teachers Toward Pedagogical Aspects in Public High Schools in Lhokseumawe City - Zahara, Syarifah Rita; Muliani, Muliani; Rahmina, Wilda; Mauritha, Siska (UIN Fatmawati Sukarno Bengkulu, 2021)
In the education quality survey issued by the PISA (Program for International Student Assessment),Indonesia is ranked 72nd out of 77 countries. The Teacher Competency Test (UKG) results in Indonesiaare still low and still far from being targeted by the government, especially in Aceh province Aceh at thenational level is still heartbreaking by being the second lowest in Indonesia. Seeing the problems faced byeducation in Indonesia, to improve the quality of education, the quality of teachers must be improvedfirst, one of which is by increasing the pedagogical competence of teachers. This study aims to know thepedagogical knowledge of physics teachers in SMA Negeri Lhokseumawe which includes aspects oflearning planning, aspects of learning methods and aspects of learning evaluation. The research wasconducted in the form of a survey with the population of this study was to take the entire physics subjectteachers at SMA Negeri Lhokseumawe, totaling 7 (seven) schools with 28 physics teachers. The samples inthis study were 3 schools that were taken by simple random sampling, namely 8 physics teachers at SMANegeri 2 Lhokseumawe, 3 physics teachers at SMA Negeri 5 Lhokseumawe, and SMA Negeri 7Lhokseumawe with 2 physics teachers. The results showed that the physics teacher's knowledge on thelearning planning aspect was in the category of having good knowledge, meanwhile the physics teacher'sknowledge on the learning method aspect already had a fairly good knowledge, while the physics teacher'sknowledge on the learning evaluation aspect also had fairly good knowledge. So it can be concluded thatphysics teachers in the pedagogical aspect are in a fairly good category, meaning that most physics teachersalready have a pretty good knowledge of pedagogical aspects.